Predictors of Preconception Care Reception in a Sample of Iranian Pregnant Women Referred to Qazvin Health Centers - Bahrami, Nasim; Allen, Kelly-Ann; Alimoardi, Zainab (Current Women's Health Reviews, 2023)
Background: Preconception care (PCC) is one of the most important components of healthcare services for women of reproductive age. Focusing on improving preconception health can lead to improved reproductive outcomes, healthier pregnancies, and healthier babies. Aims: The aim of the study was to determine the predictive factors of receiving PCC in pregnant women of Qazvin. Methods: The present cross-sectional study was conducted from March 2018 to September 2019. Participants included 350 pregnant women in their 6-14 weeks of gestation, who had been referred to a selected comprehensive health center (CHC) for their initial prenatal visits. A two-stage cluster sampling was used to access the samples with maximum socioeconomic and cultural diversity. Data were collected using a questionnaire on demographics, fertility, and factors that affect access to PCC; a questionnaire on perceived social support; and a general self-efficacy questionnaire. Data were analyzed using uni-variable and multivariable logistic regression methods with SPSS software version 25. Results: In the present study, 57.5% of the participants had received PCC. More than 75% of them received this care less than a year ago at a CHC. In the final model, wanted pregnancy (OR= 11.68), awareness of PCC (OR= 8.86), and history of ART for current pregnancy (OR= 7.18) were the strongest predictors for PCC reception. Conclusion: Women of reproductive age appear to benefit strongly from PCC services when they have planned their pregnancy and are aware of PCC services. Therefore, information related to the opportunities and potential outcomes of PCC should be made publicly available. In addition, healthcare providers should focus more on providing patients with information about preconception counseling.
Keywords: Preconception counseling